Development of a social cognitive career theory scale for measuring the intention to select surgery as a career - Hsin-Yi Chiu; Chi-Ming Chiang; Yi-No Kang; Chia-Che Chen; Chien-Chih Wu; Yu-Han Chiu; Kung-Pei Tang; Chih-Chin Kao; Po-Li Wei (Heliyon, 2023)
Background: Surgeon shortages have emerged as a prominent global issue. Although various studies have explored the factors that influence medical students in choosing surgery as a career, addressing the need for surgeons requires a multifaceted approach. However, there is currently a lack of a theoretically grounded scale to evaluate the effectiveness of surgical career development or policy promotion. Thus, this study aimed to develop a questionnaire for assessing the preference for a surgical career by adopting the Social Cognitive Career Theory (SCCT). Materials and methods: The study aimed to develop the Social Cognitive Career Theory Scale toward Surgery (SCCTSS) by adopting the framework of SCCT. The questionnaire was created through expert consensus and the content validity index (CVI) calculation. Subsequently, a pilot version of the SCCTSS was administered to 222 medical students in their clinical clerkships, and the collected data underwent item analysis. Additionally, the validation of the SCCTSS by gender was performed. Results: The SCCTSS comprised 16 items that passed expert panel evaluation, with a CVI >0.8, mean ≥ 3.00, and an interquartile range ≤1. Item analysis demonstrated that the quality of the SCCTSS met the qualifying threshold. Furthermore, the SCCTSS questionnaire effectively validated gender differences in surgical career preference. Conclusions: We developed an internally consistent and reliable scale and validated it through an expert panel method and feedback from medical students. Further research is required to evaluate the targeted interventions that may assist in recruiting medical students into the field of surgery through the application of the SCCTSS.